THE LEVEL OF A COUNTRY'S INTERNATIONAL RESERVES: A METHODICAL APPROACH AND ITS APPROBATION (Eureka Journal of Business, Economics & Innovation Studies, 2026)
In this article develops a methodological approach for determining the sufficient level of a country's international reserves and presents the results of its testing. As part of this study, recommendations have been developed for the Central Bank of the Republic of Uzbekistan to ensure the country's solvency in terms of public borrowing and stability in the foreign exchange market in the context of a dynamic increase in external debt.
Keywords: Country's solvency, external debt, stability, government borrowing, gold and foreign currency reserves, crisis, financial leverage, indicator of money supply security, monthly volume of imports, and short-term debt.